PENGARUH MANFAAT DAN KEMUDAHAN E-FILLING TERHADAP PENYAMPAIAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI PADA UPT LAPAS KELAS IIA TANJUNG RAJA - Sahila Sahila; Candra Irawan (Universitas Tridinanti, 2021)
Taxes are the main source of state revenue in financing and development. The Directorate General of Taxes is modernizing tax administration as a form of improving the quality of tax services for taxpayers, one of which is the development of tax reporting using electronic filling (e-filling). This study aims to determine the simultaneous and partial effect of two types of perceptions, namely the benefits and convenience of e-Filling on the submission of annual tax returns for individual taxpayers.This study uses primary data with the object of research being taxpayers at the Class IIA Tanjung Raja Prison and secondary data that can support the research. To determine the effect of independent variables on related variables, multiple linear regression analysis was used in SPSS V22. Based on multiple linear regression analysis, there is a simultaneous influence between the benefits of e-Filling and the ease of e-Filling on the submission of the annual SPT of individual taxpayers. Judging from the significance value (0.000 <0.05), it means that H0 is rejected and H1 is accepted. The results of the partial study between the benefits and convenience of e-Filling on the submission of the annual SPT of individual taxpayers, namely for the e-Filling benefit variable, it has a significant effect (0.000 <0.05) meaning that H0 is rejected and H1 is accepted, and for the variable of e-Filing convenience has an effect significant (0.000 < 0.05) which means that H0 is rejected and H1 is accepted. The author's suggestion is to increase promotion, socialization widely, and improve the e-Filling system.Keywords: Benefits of E-Filling, Ease of E-Filling, Submission of Annual Tax Return for Individual Taxpayers.